2015
DOI: 10.1021/la504162u
|View full text |Cite
|
Sign up to set email alerts
|

High Turnover Frequency of Hydrogen Evolution Reaction on Amorphous MoS2 Thin Film Directly Grown by Atomic Layer Deposition

Abstract: Recently amorphous MoS2 thin film has attracted great attention as an emerging material for electrochemical hydrogen evolution reaction (HER) catalyst. Here we prepare the amorphous MoS2 catalyst on Au by atomic layer deposition (ALD) using molybdenum hexacarbonyl (Mo(CO)6) and dimethyl disulfide (CH3S2CH3) as Mo and S precursors, respectively. Each active site of the amorphous MoS2 film effectively catalyzes the HER with an excellent turnover frequency of 3 H2/s at 0.215 V versus the reversible hydrogen elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
181
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(190 citation statements)
references
References 53 publications
7
181
2
Order By: Relevance
“…Increasing the MoCl 5 dose decreased the film thickness close to the precursor inlet, which hints toward etching of the deposited film by MoCl 5 . Later, we also found that Mo(CO) 6 , the other molybdenum precursor used for ALD of MoS 2 , [47][48][49][50][51][52] suffered from heavy precursor decomposition in our reactor already at 110 °C. This was avoided by lowering the temperature below 100 °C, but no film deposition was found in this case.…”
Section: Evaluation Of Published Mos 2 Processesmentioning
confidence: 72%
See 2 more Smart Citations
“…Increasing the MoCl 5 dose decreased the film thickness close to the precursor inlet, which hints toward etching of the deposited film by MoCl 5 . Later, we also found that Mo(CO) 6 , the other molybdenum precursor used for ALD of MoS 2 , [47][48][49][50][51][52] suffered from heavy precursor decomposition in our reactor already at 110 °C. This was avoided by lowering the temperature below 100 °C, but no film deposition was found in this case.…”
Section: Evaluation Of Published Mos 2 Processesmentioning
confidence: 72%
“…[34,36,37] Other bottom-up techniques used for the deposition of thin MoS 2 films include sputtering, [40] physical vapor transport, [41] pulsed laser deposition, [42] and atomic layer deposition (ALD). [43][44][45][46][47][48][49][50][51][52] Atomic layer deposition is an inherently scalable technique that can be regarded as an advanced modification of CVD. It is based on self-limiting surface reactions of vapor-phase precursors that are alternately pulsed to substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6,21,54 We then further compared the Turnover frequency (TOF) of different catalysts, which is an effective way to determine the active sites of the catalyst 10,16 ( Figure S11 for more information). The calculated TOF for OMoS 2 /rGO catalyst is 1.74, 5.15, and 7.37 s −1 at the overpotential of 220, 300, and 350 mV, respectively, which is much higher than those of our prepared O-MoS 2 (3.24 s −1 at η = 300 mV) and pristine MoS 2 /rGO (1.47 s −1 at η = 300 mV) catalysts (Table S1) and those of MoS 2 -based catalysts, such as defect-rich ultrathin MoS 2 nanosheets 4 (0.70 s −1 at η = 300 mV), amorphous MoS 2 films (0.80 s −1 at η = 220 mV) 51 and 3D MoS 2 nanospheres (0.89 s −1 at η = 350 mV). 57 Although pristine MoS 2 /rGO has lower TOF than O-MoS 2 , it exhibits better catalytic ability ( Figure 6) due to the various exposed vertically aligned edges.…”
Section: Research Articlementioning
confidence: 99%
“…[1][2][3][4] MoS 2 is an attractive and most widely studied TMDC due to its unique properties. [5][6][7] Layered MoS 2 consists of a vertical stack of 0.65 nm thick single layers, which are held together by van der Waals inter actions. Few layer MoS 2 exhibits a band gap ranging from 1.2 to 1.9 eV depending on its thickness, which is favorable prepare high quality large area TMDCs with excellent con tinuity.…”
Section: Introductionmentioning
confidence: 99%